2010
DOI: 10.1902/jop.2010.100162
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration Around Implants in Periodontally Compromised Patients: A Randomized Clinical Trial of the Effect of Immediate Implant With Immediate Loading

Abstract: Immediate loading of a single implant placed in a fresh extraction site in periodontally compromised patients resulted in similar bone gain and soft tissue esthetic outcomes compared to delayed loading. Primary closure and delayed loading to ensure bone regeneration around implants were not critical in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
96
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(101 citation statements)
references
References 29 publications
(40 reference statements)
1
96
0
4
Order By: Relevance
“…Similar to previous studies of immediately restored dental implants in periodontally treated patients [15,16] , the survival rate of dental implants was higher than 90%. These results can be compared to other studies of patients with and without a history of periodontal disease [15,17,18]. For example, the results of the present study were comparable to results of immediately restored dental implants in periodontally treated patients obtained by Horwitz et al [15] with survival rate greater than 90%.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to previous studies of immediately restored dental implants in periodontally treated patients [15,16] , the survival rate of dental implants was higher than 90%. These results can be compared to other studies of patients with and without a history of periodontal disease [15,17,18]. For example, the results of the present study were comparable to results of immediately restored dental implants in periodontally treated patients obtained by Horwitz et al [15] with survival rate greater than 90%.…”
Section: Discussionsupporting
confidence: 88%
“…In a literature review [16], implant survival rates of immediately loaded implants with immediate or delayed implant placement ranged from 95·8% to 100%. Also, in a previous study Shibly et al [17] compared bone regeneration and esthetic outcomes between immediate and conventional loading of dental implants placed immediately after extraction in patients with a history of periodontal disease, the implant survival rate at 2 years was 96.7% and 93.3% in the immediate loading and conventional loading group respectively. De Boever et al [18] evaluated the implant survival rate in periodontally non-susceptible patients and in patients with chronic adult periodontitis or with generalized aggressive periodontitis, implant survival in the periodontally non-susceptible patients and chronic adult periodontitis group was 98% and 96% after 140 months (showing no difference), but only 80% after 100 months in the generalized aggressive periodontitis group .…”
Section: Discussionmentioning
confidence: 98%
“…Five studies 23,39,40,44,51 compared CBL changes in one‐ versus two‐stage IIP from 12 to 60 months. Two studies 39,40 evaluated CBL at 12 months, two up to 24 months, 23,44 and one up to 60 months 51 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies 23,39,40,44,51 compared CBL changes in one‐ versus two‐stage IIP from 12 to 60 months. Two studies 39,40 evaluated CBL at 12 months, two up to 24 months, 23,44 and one up to 60 months 51 . Four studies reported CBL at 12 months and included 126 and 128 implants in the one‐ and two‐stage groups, respectively 23,39,40,51 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation